Proceedings of the 2016 ACM Conference on Economics and Computation 2016
DOI: 10.1145/2940716.2940726
|View full text |Cite
|
Sign up to set email alerts
|

The Unreasonable Fairness of Maximum Nash Welfare

Abstract: The maximum Nash welfare (MNW) solution -which selects an allocation that maximizes the product of utilities -is known to provide outstanding fairness guarantees when allocating divisible goods. And while it seems to lose its luster when applied to indivisible goods, we show that, in fact, the MNW solution is unexpectedly, strikingly fair even in that setting. In particular, we prove that it selects allocations that are envy free up to one good -a compelling notion that is quite elusive when coupled with econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
179
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(183 citation statements)
references
References 33 publications
4
179
0
Order By: Relevance
“…NSW is scale free and it achieves a natural compromise between fairness and efficiency, see [20,6] also for other properties of NSW. Additionally, NSW is related, directly or indirectly, to several key solution concepts in game theory and economics.…”
Section: Properties Of Nswmentioning
confidence: 99%
“…NSW is scale free and it achieves a natural compromise between fairness and efficiency, see [20,6] also for other properties of NSW. Additionally, NSW is related, directly or indirectly, to several key solution concepts in game theory and economics.…”
Section: Properties Of Nswmentioning
confidence: 99%
“…These mechanisms are available for public use at no cost: users can simply log in, define what is to be divided, and enter their valuations. Since the site's launch in November 2014, there have been over 60,000 users [10]. The company Fair Outcomes, Inc. (http://www.fairoutcomes.com) offers fair division services in a similar vein.…”
Section: Applicationsmentioning
confidence: 99%
“…For example, in the case of distribution of indivisible goods on Spliddit, users know that the solution will be envy-free up to one good and Pareto optimal [10]. Our hope is that further work in the area of fair division of indivisible goods will allow user-facing services like Spliddit, Fair Outcomes, Inc., and Course Match to offer users even stronger fairness guarantees.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caragiannis et al [2016] have recently shown the MNW solution to satisfy envy freeness up to one good, as well as approximating the maximin share guarantee. However, work in fair division focuses primarily on the allocation of private goods, where each alternative gives utility to exactly one agent.…”
Section: Introductionmentioning
confidence: 99%